2014
DOI: 10.3390/s140611204
|View full text |Cite
|
Sign up to set email alerts
|

A Medical Cloud-Based Platform for Respiration Rate Measurement and Hierarchical Classification of Breath Disorders

Abstract: The measurement of human respiratory signals is crucial in cyberbiological systems. A disordered breathing pattern can be the first symptom of different physiological, mechanical, or psychological dysfunctions. Therefore, a real-time monitoring of the respiration patterns, as well as respiration rate is a critical need in medical applications. There are several methods for respiration rate measurement. However, despite their accuracy, these methods are expensive and could not be integrated in a body sensor net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 25 publications
3
43
0
Order By: Relevance
“…In this way, the optimization problem is relatively straightforward [18]. Several recent studies have demonstrated the usefulness of SVMs in the framework of SAHS management [102][103][104][105]. Moreover, in the present research, some studies were reviewed reporting that SVM-based classifiers reached higher accuracy than ANNs [23,45,52].…”
Section: Resultsmentioning
confidence: 99%
“…In this way, the optimization problem is relatively straightforward [18]. Several recent studies have demonstrated the usefulness of SVMs in the framework of SAHS management [102][103][104][105]. Moreover, in the present research, some studies were reviewed reporting that SVM-based classifiers reached higher accuracy than ANNs [23,45,52].…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers used it for classification purposes [9]. SVM use group of labeled training database to construct linear functions.…”
Section: Support Vector Machinementioning
confidence: 99%
“…Inspiratory stridor suggests extrathoratic airway obstruction, such as occurs in laryngomalacia, subglottic stenosis, and croup. Expiratory stridor suggests intrathoracic central airway obstruction, such as occurs in mass or vascular compression of trachea, tracheomalacia, and [9]. Here, DWT is discussed in section2.…”
Section: Introductionmentioning
confidence: 96%
“…In addition to the physical benefits derived from correct habits of breathing, people's mental power, happiness, self-control, clear-sightedness, morals, and even their spiritual growth may be increased by an understanding of the "Science of Breath" [5]. Recent studies exploited the advances in wearable sensing, signal processing and machine learning principles to provide innovative decision making capabilities for subjects' breathing characteristics and to discern valuable information [11].…”
Section: Introductionmentioning
confidence: 99%